Old Las Vegas : Hispanic memories from the New Mexico meadowlands - García, Nasario (Texas Tech University Press, 2005)
Oral history.
Keywords: Hispanic Americans -- New Mexico -- Las Vegas Region -- Biography.; Older people -- New Mexico -- Las Vegas Region -- Biography.; Country life -- New Mexico -- Las Vegas Region -- Anecdotes.; Country life -- New Mexico -- Anecdotes.; Folklore -- New Mexico -- Las Vegas Region.; Folklore -- New Mexico.; Oral history.; Las Vegas Region (N.M.) -- Social life and customs -- Anecdotes.; New Mexico -- Social life and customs -- Anecdotes.; Las Vegas Region (N.M.) -- Biography.; Folklore -- Nouveau-Mexique.; Histoire orale.; Nouveau-Mexique -- Mœurs et coutumes -- Anecdotes.; oral histories (literary genre); SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; Country life; Folklore; Hispanic Americans; Manners and customs; Older people; Oral history; New Mexico; New Mexico -- Las Vegas Region; Anecdotes; Biographies; Biographies.